The platelet-to-lymphocyte ratio (PLR) and the clinical impact on the outcome of stroke patients under previous aspirin therapy - Ana Catarina Pinto da Silva Alves (2022)
Background: Platelets and lymphocytes play a critical role in the pathophysiological pathways of the early stages of acute ischemic stroke (AIS). Platelet-to-lymphocyte ratio (PLR) is an accessible parameter to evaluate inflammatory response as it can be calculated from a regular hemogram. Aspirin/acetylsalicylic acid (ASA) plays a central role in the secondary prevention of cardiovascular disease, however, its impact on PLR levels and consequent prognostics are not completely understood. Aims: Explore the relationship between aspirin and PLR and the consequent effects on mortality and stroke recurrence in patients with AIS. Methods: 424 patients were included in this observational study. PLR values were calculated from the first blood sample at admission. The effect of PLR on mortality and stroke recurrence was evaluated using Kaplan-Meier methodology, log-rank test, Cox proportional hazard models, and Bootstrap Analysis. Results: Our results indicate an association of high PLR (>170) with a poor overall survival on stroke patients (HR 1.880, 95%CI 1.176 - 3.005, p = 0.008), particularly in those with no record of aspirin therapy (p = 0.018). Modeling the risk of a second event (recurrence) in the timeframe of 36 months demonstrated a predictive capacity for PLR (p=0.004) confirmed by Bootstrap analysis (p = 0.001; 1000 replications). The inclusion of PLR in simulating models' equations provides a gain of nearly 20% in the predictive ability (C-index 0.779 increases to 0.946). Conclusions: The platelet-to-lymphocyte ratio (PLR) has a link to clinical impact with worse outcomes for stroke patients and this is firstly demonstrated related to previous aspirin therapy.